Second language acquisition of intonation: Peak alignment in American English. (January 2018) - Graham, Calbert; Post, Brechtje
Highlights: We investigated the L2 acquisition of pitch accent contour, tonal alignment. Choice of pitch accent contour varied depending on L1 and proficiency level. Alignment patterns varied depending on stress position and L1, but not segmental structure. Late peaks appear to be the preferred simplification strategy by L2 learners. Highly sensitive language-specific alignment regularities appear problematic for L2 learners. Abstract: The objective of the present study was to investigate (1) whether, and to what degree, late bilinguals of different L1 backgrounds are comparable to native speakers in the phonetic implementation of tonal targets in their L2, (2) whether they exhibit general patterns of acquisition irrespective of the typological closeness of their L1 to their L2, and (3) whether learners' choice of accent contours and the alignment of the high tone (H ∗ ) proceeds in parallel with proficiency in the L2. More specifically, we examined the acquisition of the nuclear contour composition and the H ∗ alignment of the American English (L)H ∗ L- (i.e. pitch accent and boundary tone combination) in initial-stressed and final-stressed words by Japanese and Spanish late bilingual speakers at varying proficiency levels in American English. Our results show that the L1 Spanish speakers were more comparable than the L1 Japanese speakers to the native English speakers in the phonological aspect of intonation (choice of pitch accent contour). In terms of peak alignment, we found that the late bilinguals generally tended to realise significantly later alignment than the native speakers, although the precise manifestation of this varied according to the L1 background of speakers and the stress pattern of words.